Chemical Investigation of Medicinal Plants - Dayal, Rameshwar (Indian Forester, 1997)
Since his existence on this planet man has had to depend on Nature for sustenance and survival. Medicinal plants have been used by him to keep himself healthy. According to the studies on ethnomedicine and folk medicine about 2000 species are newly identified as drug yielding plants and are well known for their use in about 4000 drug industries of various Indian systems of medicine. Phytochemical examination of a number of them has been carried out and active ingredients, isolated, identified are being currently used as drugs. Chemical examination of hitherto unexplored medicinal plants will help in discovering new drugs.